Irrigation and nitrogen fertilizer increase wheat productivity by improving root-shoot population coordination - Lifang Wang; Shijie Liu; Suhao Lu; Tianyu Lv; Dongyun Ma; Guozhang Kang; Yingxin Xie; Jutao Sun; Chenyang Wang (Agricultural Water Management)
The optimization of plant root distribution plays an important role in obtaining deep soil resources, and enhancement of photosynthetic performance has been demonstrated to maintain wheat production, but the ideal water-nitrogen (N) utilization regime for winter wheat root-shoot growth remains unclear. A 2-year field experiment was conducted during the wheat growing seasons of 2020–2022, with two irrigation levels (W0, no irrigation; W1, irrigation 75 mm at jointing and anthesis stages) and three N rates (N0, 0 kg ha−1; N180, 180 kg ha−1; N300, 300 kg ha−1), N was applied before ploughing (50 %) and jointing stage (50 %). Wheat yield and yield components, leaf area index (LAI), radiative vegetation index, population canopy apparent photosynthesis (CAP), and root system architecture were examined. Irrigation significantly increased the spike number by 13.5 %, and the yield by 15.5 % (P < 0.05) with respect to W0. N fertilization increased the spike number and grains per spike by 34.3 % and 11.2 % with respect to N0. Population quality (LAI, vegetation index, and ratio vegetation index) also increased under irrigation and N treatments; W1N180 increased the canopy photosynthetic rate by 3.5 %–12.8 % with respect to W1N300. Structural equation modeling indicated that root dry weight density (RWD) had a direct positive effect on CAP, whereas CAP and root-shoot ratio had significant effects on yield, and the physiological efficiency of N had direct negative effects on changes in grain yield. Therefore, W1N180 treatment may be considered the optimal management practice for resource use efficiency and environmental benefits of sustainable agricultural development.